PREDICTING SEVERITY AND VISUAL OUTCOMES OF EYE TRAUMA FOLLOWING TREATEMENT, USING OCULAR TRAUMA SCALE - Teyyeb Azeem Janjua (Army Medical College Rawalpindi, 2020)
Objective: To predict the severity and visual outcomes following treatment in patients sustaining eye trauma using ocular trauma scale.